Analisis instrumen asesmen ipa berdasarkan teori berpikir kritis facione kelas V sekolah dasar - Putri, Levita Nuraeni; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy; Saputri, Ilmy (Jurnal Pendidikan Dasar, 2021)
This research aims to describe the results of a science instrument analysis based on Facione's critical thinking theory. The method used in this study was qualitative descriptive. The research subject was a 5th grade science instrument of Angkasa Colomadu Elementary School. Data collected with document analysis and interview. The validity test used for the data was technical triangulation. This research using Miles and Huberman's data-analysis techniques of data collection, data reduction, data display, and conclusions. Analysis result shows that the science instrument went in less than the criteria with a 29.91% score. Based on each analysis of critical thinking indicator of Facione for the 5th grade science's final semester exam (PAS) of Angkasa Colomadu Elementary School, the dividend score on an interpretation indicator of 5.83% in the category has not met; Undermeeting category of 22.22% analysis indicator; 10.56% evaluation indicator with category not met; 25.01% inference indicator with less than met category; 15.83% explanation indicators in unmet categories; And a 100% self-regulation indicator with a very well-met category. Therefore, Facione's critical thinking indicator was inadequate. This study can be used as a reference for teachers, school, and the government to optimize the quality of assessment and students critical thinking skills.